How Does the Pinatubo Eruption Influence Our Understanding of Long-Term Changes in Ocean Biogeochemistry? - Olivarez, Holly C.; Lovenduski, Nicole S.; Eddebbar, Yassir A.; Fay, Amanda R.; Mckinley, Galen A.; Levy, Michael N.; Long, Matthew C. (Geophysical Research Letters, 2024)
Pinatubo erupted during the first decadal survey of ocean biogeochemistry, embedding its climate fingerprint into foundational ocean biogeochemical observations and complicating the interpretation of long-term biogeochemical change. Here, we quantify the influence of the Pinatubo climate perturbation on externally forced decadal and multi-decadal changes in key ocean biogeochemical quantities using a large ensemble simulation of the Community Earth System Model designed to isolate the effects of Pinatubo, which cleanly captures the ocean biogeochemical response to the eruption. We find increased uptake of apparent oxygen utilization and preindustrial carbon over 1993-2003. Nearly 100% of the forced response in these quantities are attributable to Pinatubo. The eruption caused enhanced ventilation of the North Atlantic, as evidenced by deep ocean chlorofluorocarbon changes that appear 10-15 years after the eruption. Our results help contextualize observed change and contribute to improved constraints on uncertainty in the global carbon budget and ocean deoxygenation. Oceanographers' understanding of ocean properties comes from research cruises that take scientific measurements in the same locations every ten years. However, the first of these research cruises were deployed just after a large volcanic eruption in 1991 called Pinatubo. The eruption cooled the planet for several years, including the upper ocean. Here, we investigate how this eruption affected ocean properties using two collections of simulations of the Community Earth System Model which is a mathematical representation of the Earth system. The first collection of simulations shows the response to the eruption, while the second collection shows how ocean properties would have changed if there had been no eruption. The difference thus tell us the influence of the eruption on ocean properties. We find an increase of oxygen and preindustrial carbon over 1993-2003 due to Pinatubo, as well as an increase of ventilation of the North Atlantic that appears ...